1635 : the Dreeson incident - Flint, Eric (Ring of fire (Riverdale, N.Y.), 2008)
While the old entrenched rulers and manipulators continue to plot against this new upstart nation, everyday life goes on in Grantville, the town lost in time, with librarians, firefighters, and garbage collectors trying to make do under unusual circumstances. And what better place for an undercover spy from France than working with the garbage collectors, examining 20th century machines that others throw out and copying the technology (though he wishes one device<U+2014>the paper shredder<U+2014>had been left behind in the future). There are more sinister agents at work, however. One of them, Ducos, almost succeeded in assassinating the Pope, but his plan was ruined by quick action by a few Americans. Now, the would-be assassin not only has a score to settle, but has also decided on two excellent targets: Grantville's leader Mike Stearns and his wife Rebecca. . .